Effect of structural disparity of graphene-based materials on thermo-mechanical and surface properties of thermoplastic polyurethane nanocomposites. (16th June 2017) - Bera, Madhab; Maji, Pradip K.
Abstract: Nanocomposites based on thermoplastic polyurethane (TPU) and graphene-based materials such as graphene oxide (GO) and reduced graphene oxide (RGO) was synthesized by in-situ solution polymerization technique. The effect of structural differences between GO and RGO in the thermo-mechanical and surface properties of TPU at ultralow concentration was the foremost aspiration of this work. TPU/GO nanocomposites exhibited superior mechanical properties compared to TPU/RGO nanocomposites at very low loading. With the incorporation of 0.10 wt% of GO, the resultant nanocomposite showed 280% increase in tensile strength and 410% increase in toughness. Interestingly, the elongation at break nanocomposite increased from 588% for pristine TPU to 1006% for TPU/GO-0.10. Property improvement of RGO filled nanocomposite was not so prominent as compared to GO filled nanocomposites. Thermal stability of the nanocomposites as examined by thermogravimetric analysis (TGA) depicted a 12 °C increase in thermal stability for 0.2 wt% GO filled nanocomposite whereas the same for RGO filled nanocomposite was only 6 °C. Contact angle study revealed that the RGO filled nanocomposites were becoming more hydrophobic whereas GO filled nanocomposites films showed the opposite trend. Graphical abstract: Highlights: Discussed the structural disparity of GO and RGO on the properties of thermoplastic polyurethane. Huge improvement in thermo-mechanical properties at ultra-low loading. Structure-property co-relation established in polyurethane nanocomposites. Different nature of composite surfaces was highlighted.